A comparative analysis of the divisia index and the simple sum monetary aggregates for South Africa - Moyo, Solomon Simbarashe (Rhodes University, Faculty of Commerce, Department of Economics, 2009)
The effectiveness of monetary policy in achieving its macroeconomic objectives such as price stability and economic growth depend on the monetary policy tools that are implemented by the Central Bank. Monetary aggregates are one of the tools that have been used as indicators of economic activity and as intermediate targets to achieve these economic objectives. Until recently, monetary aggregates have been questioned and criticised on their usefulness in monetary policy. This has been attributed to the economic, financial and technological developments that have distorted the relationship between monetary aggregates and major macroeconomic variables. This study investigates the relevance of monetary aggregation by comparing the traditional simple sum and Divisia index monetary aggregates which was constructed for the first time for South Africa using the Tornquist-Theil method. The Polynomial Distributed Lag model is employed to compare the performance of these monetary aggregates using their relationship with inflation and manufacturing index. Furthermore, the aggregates are compared in terms of their controllability and information content. Overall, the study found a very strong relationship between inflation and all the monetary aggregates. However, more specifically the results suggested that the Divisia indices are superior to the simple sum in terms of predicting inflation. The evidence further suggests that the Divisia aggregates provide higher information about inflation than the simple sum aggregates. Regarding the controllability of the monetary aggregates, the findings suggest that the monetary authorities can hardly control the monetary aggregates using monetary base. Finally, the relationship between manufacturing index and all the monetary aggregates was very weak.
Keywords: Monetary policy -- South Africa; Money supply -- South Africa; Inflation finance -- South Africa; Index numbers (Economics)